CODE OF SOCIAL CONDUCT OF THE LOWER-TEREK COSSACKS (XIX - EARLY XX CENTURY) - Gimbatova, M B (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the traditional social norms and moral foundation of the Lower Terek Cossacks. The author presents communication possibilities, codes of gender-based behavior, stereotypes and patterns of male and female behavior in the society and their place in the public social space. Optimal standards and models the correct behavior were followed in the society, any deviant behavior or behavior disorder were condemned, and in some cases resulted in the exclusion from the community.
Keywords: Lower Terek Cossacks; Cossack circle; code of conduct; society; morality; traditions; greeting; treatment; prohibition